Effective implementation of the 'Seeds Without Borders' agreement in South Asia - CGIAR Research Program on Rice (2020)
A policy dialogue was organized and a book published about the effective implementation of the "Seeds Without Borders" Agreement and to encourage more countries to join the Agreement.